Measuring corruption in the EU - Vanhauwaert, Rosita (European crime prevention monitor, 2014)
In this fifth monitor the European Crime and Prevention Network focusses on corruption. Corruption is estimated to cost the EU economy 120 billion EUR per year. It does not only hamper economic development, but also undermines democracy, and damages social justice and the rule of law in general (European Commission, 2014). It is a broad, complex and multifaceted phenomenon, which covers a wide range of phenomena. Therefore it is not easy to get an overview of the phenomenon. To amend this, this monitor report provides an overview of the relevant existing data available on corruption at the EU level and also focuses on the main trends and levels of perceptions, experiences and recorded levels of corruption in the EU Member States.